ANALISIS FAKTOR INTERNAL DAN FAKTOR EKSTERNAL UMKM OLAHAN IKAN DI KABUPATEN REMBANG DENGAN MENGGUNAKAN ANALISIS SWOT - Dian Anita Sari; Agus Widodo (Sekolah Tinggi Ilmu Ekonomi YPPI Rembang, 2021)
Coronavirus Disease 2019 (COVID-19) which emerged in 2020 has an impact on many countries including Indonesia. Pakpahan (2020) stated that the sectors implicated in Indonesiaare tourism, trade and investment. The business sector in Indonesia is dominated by Micro, Smalland Medium Enterprises (MSMEs). The purpose of this research is to study internal factors andexternal factors that support the competitiveness of processed fish MSMEs in Rembang Regencyin the midst of the COVID-19 pandemic. The research methodology uses SWOT analysis. Theresults of the SWOT analysis show that internal factors have a score of 5.80 while externalfactors have a score of 6.42.